A new mathematical simulation to study flip turn characteristics in front crawl swim - Shahbazi-Moghaddam, M.; Sanders, R. H. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
Swim turns represent an integral factor in determining the final outcome of a swimmer race. The aim of present study was to provide a comprehensive mathematical modelling for achieving kinematic parameters in freestyle flip (pike) turn. In proposed model all attempts have been applied to find out what swimmers should do in order that the turns are accomplished in shorter time. This new mathematical model has been adopted to flip turn but can also be adopted to tuck turn with minor change in calculations. Theoretical considerations suggest that faster upper limbs rotation could lead to a torso pressure gradient, which would induce significant axial flow along the upper limbs toward the torso. Our results demonstrate a better reality of the predicted rotational of body during front crawl swim flip turn. In this new model, we hypothesize that in flip turn the body can be considered and simulated as three thin hinged prisms; upper body, thigh, and shank.